2021
DOI: 10.34172/ijhpm.2021.171
|View full text |Cite
|
Sign up to set email alerts
|

Dropout Analysis of a National Social Health Insurance Program at Pokhara Metropolitan City, Kaski, Nepal

Abstract: Background: Nepal’s national social health insurance (SHI) program, which started in 2016, aims to achieve universal health coverage (UHC), but it faces severe challenges in achieving adequate population coverage. By 2018, enrolment and dropout rates for the scheme were 9 percent and 38 percent respectively. Despite government's efforts, retaining the members in SHI scheme remains a significant challenge. The current study therefore aimed to assess the factors associated with social health insurance program dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Furthermore, a scaled scenario of the Pokhara metropolitan Kaski district also showed that the dropout proportion is as high as one-fifth, as revealed by Sharma et al ( 26 ), which is nearly double our study (9.1%). This may show in high dissatisfaction among families, especially among urban dwellers.…”
Section: Discussion and Prospectssupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, a scaled scenario of the Pokhara metropolitan Kaski district also showed that the dropout proportion is as high as one-fifth, as revealed by Sharma et al ( 26 ), which is nearly double our study (9.1%). This may show in high dissatisfaction among families, especially among urban dwellers.…”
Section: Discussion and Prospectssupporting
confidence: 78%
“…This may be obvious when we ignore the extraneous factors in communication and behavior between the beneficiaries and the HCPs. Furthermore, in the same line, a dropout analysis carried out in Pokhara metropolitan showed moderate odds (OR, 3.09; 95%CI, 1.01–9.49) of dropout due to unfriendly behavior of HCP ( 26 ). This may indicate that there is a sheer of background variables behind the poor beneficiary-provider communication, such as perceived opportunistic behavior of the insureds by providers and, thus, deviating toward the uninsured, long waiting time, poor patient management, and unmet expectations of the beneficiaries.…”
Section: Discussion and Prospectsmentioning
confidence: 76%
See 2 more Smart Citations
“…Almost 3 out of 10 (28.2%) of the insurees recorded dropped out of HIPs in Pokhara (a major metropolitan city in Nepal and capital of the Gandaki Province), which indicated that there has been a major challenge to the sustainability of the new HIP (Sharma et al, 2021). According to HIB, people's participation in enrolling in the new HIPs remains low (HIB, 2020), and the rate of dropout is high.…”
Section: Introductionmentioning
confidence: 99%